Oplemenitenje orodij za stiskanje kovinskih prahov - Torkar, Matjaž (Kovine zlitine tehnologije, 1999)
Modern trends in development of tools are oriented towards the surface modification with one or multi layer hard coating. Experiences with vcuum heat treatment of HSS steel Č 7680 (BRM2) show that optimizing of vacuum heat treatment prolongs the tool service life. Hard coatings give additional contribution to prolongation of tool service life. The tools for metal powder pressing were vacuum heat treated, pulsed plasma ion nitrided and coated with TiN or CrN by PVD process. Different combinations of surfacing were tested on industrial tools during normal production in Unior Zreče. The results show that surfacing of tested tools prolongs their lifetime for at least two times.
Keywords: jekla; površine; trde prevleke; nitriranje; orodje